2005
DOI: 10.1111/j.1462-5822.2005.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of hyphae and hypha-co-regulated genes to Candida albicans virulence

Abstract: SummaryThe fascinating ability of Candida albicans to undergo dramatic changes in cellular morphology has invited speculation that this plasticity in form contributes to the virulence of the organism. Molecular genetic analyses have confirmed this hypothesis and further demonstrated that genes that govern cellular morphology are co-regulated with genes encoding conventional virulence factors such as proteases and adhesins. The transcriptional regulatory networks of C. albicans thus ensure that hyphae are produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
319
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(335 citation statements)
references
References 50 publications
(91 reference statements)
10
319
1
5
Order By: Relevance
“…In C. albicans, GlcNAc induces the formation of hyphal cells, which is an underlying virulence trait as budding and hyphal cells are thought to carry out unique roles during infection. In addition to different morphologies, budding and hyphal cells differ in the expression of virulence factors (Nantel et al, 2002;Lorenz et al, 2004), such as adhesin proteins, secreted hydrolytic enzymes, and antioxidant enzymes (Hube, 2004;Whiteway and Oberholzer, 2004;Kumamoto and Vinces, 2005). Therefore, in this study we used mass spectrometry to identify plasma membrane proteins in budding cells and GlcNAc-stimulated hyphae, which have the potential to mediate interaction with the host environment and contribute to the infectious process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. albicans, GlcNAc induces the formation of hyphal cells, which is an underlying virulence trait as budding and hyphal cells are thought to carry out unique roles during infection. In addition to different morphologies, budding and hyphal cells differ in the expression of virulence factors (Nantel et al, 2002;Lorenz et al, 2004), such as adhesin proteins, secreted hydrolytic enzymes, and antioxidant enzymes (Hube, 2004;Whiteway and Oberholzer, 2004;Kumamoto and Vinces, 2005). Therefore, in this study we used mass spectrometry to identify plasma membrane proteins in budding cells and GlcNAc-stimulated hyphae, which have the potential to mediate interaction with the host environment and contribute to the infectious process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, small buds are more likely to disseminate in the bloodstream and hyphal cells may be better suited for invasive growth into tissues. The distinct cell types also differ in their production of virulence factors, such as the adhesin proteins that mediate attachment to host cells and secreted hydrolytic enzymes that facilitate invasive growth (Whiteway and Oberholzer, 2004;Kumamoto and Vinces, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…13 A explicação para o fato de C. albicans apresentar os maiores percentuais de recuperação pode estar relacionada à sua grande adaptabilidade e versatilidade patogênica. 14 Ainda em nosso estudo, conduzido em Pouso Alegre, sul de Minas Gerais, foi possível observar que o número de amostras de hemocultura que o Laboratório de Microbiologia recebe, é homogêneo, sofrendo pouca variação no decorrer da pesquisa.…”
Section: Discussionunclassified
“…However, the molecular determinants of this differentiation have not yet been identified, mostly due to the lack of genetic tools for targeted disruption. Serum is also the most effective inducer of filamentous growth in C. albicans, and the signal transduction pathways activated by serum have been well characterized in this organism (for a review see Kumamoto & Vinces, 2005). Early investigations in C. albicans suggested that the serum inducing factor(s) was heat stable and nondialysable, and that the peak of serum induction activity co-migrated with the serum albumin fraction in gel filtration purification assays (Barlow et al, 1974;Buckley & Van Uden, 1963;Reynolds & Braude, 1956).…”
Section: Introductionmentioning
confidence: 99%